POWER RELATION IN ‘IF HE WANTS TO COME HOME, JUST COME HOME’: JOKOWI AIDE SAYS ABOUT RIZIEQ BY THE JAKARTA POST - Clara Ivana (Universitas Suryakancana, 2021)
This research investigated the power relation which exists in Rizieq’s homecoming case in The Jakarta Post by doing Foucauldian genealogical discourse analysis proposed by Carabine (2001). The research was also supported by evidence gained using linguistics theory, Systemic Functional Grammar, focusing on transitivity. An article entitled ‘If he wants to come home, just come home’: Jokowi Aide Says about Rizieq written in the Jakarta Post is the main discourse analyzed supported by other discourses to show an inter-relationship between discourses and counter-discourses. The findings indicate that the absence of Habib Rizieq in Indonesia is the effect of power existing around him. There are some Actors mentioned in the discourse: the government, leader of FPI, presidential chief of staff, deputy secretary-general of NU, spokesman of the 212 Alumni Association, and Prabowo. The use of transitivity evokes the position possessed by them in which they have a connection around Rizieq’s case.